IMPLEMENTASI PROGRAM SMART CITY DALAM KONTEKS PELAYANAN PUBLIK DI KABUPATEN BUTON - Arifin Utha; Saidin; Lathifa Aprilia Nur Ahmad; La Ode Aslim (Journal Publicuho, 2025)
This study aims to determine how the Smart City Program is implemented in Buton Regency, specifically in terms of the program's implementation approach and the factors that contribute to the success of its implementation in Buton Regency. The method used in this study is qualitative. The data collection techniques employed in this study include interviews, observation, and documentation. The results of the study indicate that the implementation of the Smart City Program in the context of public services still faces various obstacles, so it has not run optimally. Although there is a fairly good commitment, the main obstacles lie in the absence of a special integrated organisation, differences in perceptions between agencies, limited infrastructure, human resources, and budget, and a lack of direct communication with the community. Therefore, institutional strengthening, increased coordination, technical and resource improvements, and bureaucratic reform are needed so that the Smart City program can be implemented effectively and sustainably.